A case of late-onset sporadic hemiplegic migraine. Issue 10 (October 2019) - Yang, Xiu-Yan; Du, Hua-Ping; Xu, Yuan
Sporadic hemiplegic migraine is a rare form of migraine headache with aura. We herein report a case of visual impairment, dizziness, and motor weakness in a patient who had experienced recurrent headache attacks with aura including flickering spots and blurred vision for 20 years, Electroencephalography, cerebrospinal fluid analysis, and brain imaging findings were normal. The patient gradually recovered after treatment with nonsteroidal anti-inflammatory drugs and flunarizine.